Influence Factors of Reproductive Organ Maintenance Among Adolescent Girls in Coastal Areas - Yuliani, Armyla Eka Wahyu; Nafisah, Lu'lu; Hariyadi, Bambang (Poltekkes Kemenkes Tanjung Karang, 2024)
Adolescent girls are vulnerable to reproductive health problems such as vaginal discharge and reproductive tract infections, which are triggered by poor maintenance of their reproductive organs. This may further impact adolescents' quality of life and productivity. Adolescents in coastal areas tend to have limited sources of information, parental support, and inadequate health facilities related to adolescent reproductive health. This study aims to determine the factors that influence the behavior of maintaining reproductive organs among adolescent girls in coastal areas in the Buluspesantren District. Method: This research uses quantitative methods with a cross-sectional approach. The research population was 859 adolescent girls in coastal regions of Buluspesantren District, and a total sample of 96 respondents were selected through purposive sampling. Data were analyzed univariate, bivariate, and multivariate. There is a relationship between the availability of facilities and infrastructure (p-value=0.049) and attitudes (p-value=0.012) with reproductive organ maintenance behavior among adolescent girls in coastal areas in Buluspesantren District. The most influential factor is attitude (p-value = 0.018) with Odds Ratio (OR)=3.004. Adolescent girls with a positive attitude are 3.004 times more likely to have good reproductive organ maintenance behavior than adolescent girls with a negative attitude. Adolescent girls need to get information on reproductive organ maintenance from various trusted sources so that they have a positive attitude toward reproductive organ maintenance behavior.